Gene‐level genome‐wide association analysis of suicide attempt, a preliminary study in a psychiatric Mexican population - González‐Castro, Thelma Beatriz (Mol Genet Genomic Med, 2019)
BACKGROUND: Evidence suggests that liability for suicide behavior is heritable; additionally, suicide has been partly related to other psychiatric disorders. Nevertheless, most of the information reported so far address Caucasian and Asian individuals. Hence, our aim was to conduct a gene‐level association study in Mexican psychiatric individuals diagnosed with suicide attempt. METHODS: We recruited 192 individuals from two clinical centers in Mexico. All participants were born in Mexico and had Mexican parents and grandparents. Direct genotyping was performed using the commercial platform Infinium PsychArray BeadChip. A p‐value lower than 1e‐05 was considered as gene‐level significant and a p‐value lower than 1e‐04 was considered as gene‐level nominal significant. RESULTS: Our analyses showed that SCARA5 was associated to suicide intent at a gene‐level with statistical significance (p‐value = 1.12e‐6). Other genes were nominally associated with suicide attempt: GHSR (p‐value = 0.0004), RGS10 (p‐value = 5.13e‐5), and STK33 (p‐value = 3.62e‐5). Regarding gene variant analyses, the SNPs with a statistical association (p > .05) were rs561361616, rs1537577, rs11198999 for RGS10, and rs11041981, rs11041993, rs11041994, rs11041995, rs11041997, rs10840083, rs10769918 for STK33. For these genes, previous studies have associated SCARA5 with depression, GHSR with alcohol dependence and depression, and RGS10 with schizophrenia and depression. To date, STK33 has not been associated with any psychiatric disorder. CONCLUSION: Our outcomes revealed that SCARA5, GHSR, RGS10 and STK33 could be considered as risk biomarkers for suicide attempt behavior in our Mexican psychiatric sample. We recommend to perform larger scale analyses to have conclusive results.